DIVERSION ORDERS IN THE REPUBLIC OF SERBIA - Kovačević, Milica (Law - Theory and Practice, 2012)
Diversion model of reaction towards juvenile crime has been introduced into the Serbian criminal law system by the implementation of diversion orders. Serbian Law on Juvenile Offenders and Criminal Protection of Juveniles has enabled the application of various types of diversion orders as a novelty in juvenile criminal law of the Republic of Serbia. Diversion orders constitute a specific category of measures which can be applied both by the juvenile judge and by the public prosecutor for juveniles, in order to avoid, or to suspend, criminal proceedings towards juvenile offenders. Certain elements of the internationally acclaimed concept of restorative justice have been introduced into the Serbian criminal law system by the application of diversion orders. Therefore, the goal of this paper is to present the main features of diversion orders.